Administrations of young betelnut fruit extract (Areca cathecu l.) increased testosteron concentration in old male wistar white rat (Rattus norvegicus) - Dessy Indriana Hatta; Wimpie Pangkahila; I Gede Made Aman (Fakultas Kedokteran Universitas Udayana, 2019)
Background: With increasing age, testosterone level is tend to and cause sexual dysfunction disorders such as erectile dysfunction, sexual arousal disorders, ejaculatory disorders, orgasm disorders to infertility. Young betel nut extract (Areca catechu L.) is an herbal plant that can increase sexual arousal (libido) which has many nutrients including antioxidants. The purpose of this study was to prove that administration of young areca fruit extract could increase testosterone levels in old male wistar white rats (Rattus norvegicus). Method: This study was an experimental study using a pretest-posttest control group design that used 16 wistar male rats (Rattus norvegicus) aged 18 months old, weighing 225-250 grams divided into 2 (two) groups, namely the control group (Placebo ) and the treatment group who were given young betel nut extract 100 mg / kgBB / day (P1). The study was conducted for 28 days followed by blood sampling for testosterone levels. Results: The results showed significant increase in testosterone levels in treatment group compared to the control group, (p= <0.05)). The testosterone level increased from 14.813 ± 1.343 ng/ml before treatment to 19.602 ± 1.345 ng/ml after treatment. Conclusion: Based on the results of the analysis it can be concluded that the administration of Areca catechu L. extract can increase Testosterone levels in old male wistar white rats (Rattus norvegicus).